2011
DOI: 10.3171/2010.9.peds10326
|View full text |Cite
|
Sign up to set email alerts
|

Encephalocele in Uganda: ethnic distinctions in lesion location, endoscopic management of hydrocephalus, and survival in 110 consecutive children

Abstract: Object This study characterizes the first clinical series of encephalocele (EC) from East or Central Africa, and is the largest reported from the African continent. The authors explored survival, the efficacy of primary endoscopic management of associated hydrocephalus, and ethnic differences in EC location. Methods One hundred ten consecutive children presented to CURE Children's Hospital of Uganda for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 35 publications
2
42
1
1
Order By: Relevance
“…The frequency of 9 cases/year of the association of hydrocephalus with neural tube defect observed in our study is as high as that observed by other authors in Africa: De Paul et al [1] in Cameroon (9 cases/year) and Warf et al [2] in Uganda (22 cases/year). In Saudi Arabia, Alshail et al [3] found a higher frequency of 59.83 cases/year.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The frequency of 9 cases/year of the association of hydrocephalus with neural tube defect observed in our study is as high as that observed by other authors in Africa: De Paul et al [1] in Cameroon (9 cases/year) and Warf et al [2] in Uganda (22 cases/year). In Saudi Arabia, Alshail et al [3] found a higher frequency of 59.83 cases/year.…”
Section: Discussionsupporting
confidence: 74%
“…The treatment of these conditions (hydrocephalus, cephalocele, spina bifida) is surgical and is well established when performed separately [1, 2]. This is not the case for the association of neural tube defects with hydrocephalus in the same patient.…”
Section: Introductionmentioning
confidence: 99%
“…14, [16][17][18][19]22,23 The patient populations in Uganda and the US are different in some important respects. First, the most common cause of infant hydrocephalus in Uganda is neonatal ventriculitis, rare in North America, for which the pathogenesis remains obscure.…”
Section: Discussionmentioning
confidence: 99%
“…9,12,14,15,18 Over the past decade, ETV/ CPC has become an increasingly common treatment for infant hydrocephalus in Africa, North America, Asia, and Europe. 2,4,5,8,20 Proposed mechanisms by which CPC promotes ETV success include decreasing CSF production and altering CSF dynamics.…”
mentioning
confidence: 99%